1983
DOI: 10.2151/jmsj1965.61.3_375
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effect of CCN on the Size Distribution of Cloud Droplets

Abstract: The effect of cloud condensation nuclei (CCN) on the production of large cloud droplets in a shallow cumulus cloud was studied by numerical modeling. Dynamical processes were treated in an Eulerian framework in an axially symmetric model. Microphysical processes in the layer near cloud base were treated in a Lagrangian framework using air-parcels which ascend successively, in order to avoid the influence of artificial broadening of droplet size distribution on the formation of large cloud droplets. Following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…Our results suggest, as do others (Kuba and Takeda, 1983;Cooper et al, 1997;Feingold et al, 1999;Saleeby and Cotton, 2004), that the effects of hygroscopic seeding can vary with the background CCN number concentrations (not shown in this paper) and updraft velocity at the cloud base (or cloud types) as well as the sizes and amounts of seeding particles and the timing of seeding (not shown in this paper). Therefore, more observational data must be collected on background CCN number concentrations and cloud-base updraft velocities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results suggest, as do others (Kuba and Takeda, 1983;Cooper et al, 1997;Feingold et al, 1999;Saleeby and Cotton, 2004), that the effects of hygroscopic seeding can vary with the background CCN number concentrations (not shown in this paper) and updraft velocity at the cloud base (or cloud types) as well as the sizes and amounts of seeding particles and the timing of seeding (not shown in this paper). Therefore, more observational data must be collected on background CCN number concentrations and cloud-base updraft velocities.…”
Section: Discussionsupporting
confidence: 84%
“…Figure 3 shows the wind field at the time of peak updraft velocity for the shallow convective cloud case (a) and the stratiform cloud case (b). Kuba and Takeda (1983), Cooper et al (1997), Feingold et al (1999), and Saleeby and Cotton (2004) showed that giant CCN have the greatest effect on the precipitation efficiency of warm rain clouds in cases with numerous small background CCN. When low concentrations of small CCN are present, adding giant CCN results in a slight decrease in rainfall, suggesting that almost all rainwater is produced by condensation onto small CCN.…”
Section: Numerical Experimentsmentioning
confidence: 98%
“…The cloud parcel model used in this study has been explained elsewhere [Takeda and Kuba, 1982;Kuba and Takeda, 1983;Kuba et al, 2003]. Here the calculation scheme has been modified from the previous versions by calculating the growth and activation of particles by κ-Köhler theory.…”
Section: Cloud Parcel Modelmentioning
confidence: 99%
“…Moreover, this will be a key technique for understanding the rainout mechanisms of pollutants and optical properties of clouds. In addition, information about the size distribution of cloud droplets is an important factor for estimating the precipitation efficiency of clouds and the chemical composition of rain (Kuba and Takeda, 1983).…”
Section: Introductionmentioning
confidence: 99%